Safeguarding the Third Pole: problems, challenges, and possible solutions in the Hindu Kush Himalaya - Chaudhary, S.; Nepal, Santosh; Hussain, A.; Bhuchar, S. (Elsevier, 2024)
The Hindu Kush Himalaya (HKH), the highest mountain biome, is a global asset and supports the lives and livelihoods of nearly 2 billion people. The region is an important repository of aesthetic, biological, and cultural diversities, and contains all or part of 4 of 36 “Global Biodiversity Hotspots.” The HKH is also referred as the “Third Pole” for having the largest concentration of frozen water in the world after the two poles, with an estimated 60 cubic kilometers volume of ice, and also for containing the headwaters of 10 large Asian river systems—the Amu Darya, Brahmaputra, Ganges, Indus, Irrawaddy, Mekong, Salween, Tarim, Yangtze, and Yellow rivers. As such, the region provides varied ecosystem services to around 1.9 billion people living within the HKH and in the river basins downstream. However, the HKH faces various issues and associated challenges such as climate change, water-induced disasters, ecosystem degradation, high rates of poverty and food insecurity, marginalization, outmigration, and environmental changes. Yet, the region has a high potential for addressing these challenges in a sustainable way. This chapter discusses the existing issues, impacts, and associated challenges in the region. In doing so, we discuss transboundary landscape and river basin management, including springshed management, and the revitalization of traditional food systems as multiscale and nature-based interventions that can help in adapting to a changing environment, build transformative resilience, and deliver sustainable and inclusive development in the region.